Pengaruh Layanan Konseling Kelompok dengan Teknik Kontrak Perilaku untuk Mengurangi Prokrakstinasi Akademik Siswa Kelas VIII di SMP Negeri 3 Pangkajene - Ramadhani, Syahruni; Samad, Sulaiman; Rosmini, Rosmini (Indonesian Journal of School Counseling: Theory, Application, and Development, 2022)
Academic procrastination is the tendency to delay starting or completing academic tasks caused by irrational thoughts. Many students only intend to complete assignments within a specified period of time but they have no motivation to start. Because of his attitude, students who do procrastination will experience losses and must accept the consequences, such as low self-esteem and even fail in the academic field. A behavioral contract is the agreement and outcome of an agreement by two or more people (counselor and client) that aims to change the client's behavior and if the client is able to change his behavior, then the client will receive a reward. After group counseling services using student behavioral contracts can reduce academic procrastination behavior.